Business environmentalism strategy, competitive advantage and organisational performance in Malaysian hotel industry / Junaidah Jaidi - Jaidi, Junaidah (Institute of Graduate Studies, UiTM, 2018)
As the today’s tourists are becoming increasingly concerned with the environment and environmental products, the management teams within the hotel industry believe that the integration of environment aspects into their business strategies will lead to better organisational performance. Hotel managers believe that the environmental integration is able to create value and competitive advantage. This research, which is grounded in the resource-based view, examined the relationship between business environmentalism strategy (corporate environmentalism and environmental management accounting practices) and organisational performance among Malaysian hotels. This research further examined the mediating role of competitive advantage on the link between environmental business strategy and organisational performance. Employing the simple random technique, data were collected from 122 hotel managers from 3 to 5-star hotels in Malaysia. The data was analysed using the Partial Least Squares (PLS) approach to Structural Equation Model (SEM). Results of the hypotheses testing showed that all seven hypotheses were supported. Thus, it was concluded that both corporate environmentalism and environmental management accounting practices have a positive and significant relationship with organisational performance. It was also found that competitive advantage partially mediated the relationship between corporate environmentalism and environmental management accounting practices with organisational performance…